Framework for Economic Potential Analysis of Marine Transportation: A Case Study for Route Choice Between the Suez Canal Route and the Northern Sea Route. Issue 6 (June 2023) - Wang, Yangjun; Zhang, Ren; Liu, Kefeng; Fu, Delong; Zhu, Yingqian
This paper presents a new framework for economic analysis of marine transportation, where uncertainty is given more attention than in the current research. A new quantitative method combined with the importance ranking method is used to access the uncertainty of evidence and for fusion of evidence from multiple sources. The Bayesian network model is chosen as a tool to convey the uncertainty from one variable to another variable. Finally, with the help of information flow method, key factors are selected for sensitivity analysis. This framework is applied to a case study of maritime transportation from Shanghai to Rotterdam, aiming to investigate the economic potential of the Arctic routes and to explore the possibility of Arctic routes as a substitute for the traditional routes. A well-trained Bayesian network shows that the traditional routes will still dominate marine transportation in the near future. Sensitivity analysis reveals the asymmetric impact of key factors on the plan choice.